Impact of Business Management Implementation Based on Quality Culture on The Performance of Educators at Widya Karya Taman Vocational School Sidoarjo - Meithiana Indrasari; Siti Kasanah; Daniel Susilo (PT. EQUATOR SINAR AKADEMIA, 2023)
The aim of this study is to determine the impact of culture-based administrative management quality which includes planning, organizing school administration with a quality culture, implementing content standards, implementing process standards, and administering school infrastructure standards simultaneously which have a significant effect on teacher performance at Widya Karya Taman Sidoarjo Vocational School. This type of research was used quantitative, with a total sample of 84 teachers at Widya Karya Taman Sidoarjo Vocational School, with total sampling, with the analysis technique used using multiple linear regression with t test and F test tools. Partial and simultaneous research results show that quality culture-based administrative management includes planning, organizing school administration with a quality culture, implementing content standards, implementing process standards, and administering school infrastructure standards simultaneously has a significant effect on teacher performance, this is evidenced by a significance value of <0.05. It is hoped that the results of this study can improve the quality of human resources capable of playing a role in administrative management with a culture of quality. In an effort to increase administrative professionalism, it is necessary to develop collegial supervision, in addition to the supervision activities that have been carried out all this time.